What a time to be working for a drugs harm reduction agency! (Concept: The Journal of Contemporary Community Education Practice Theory, 2020)
Like other voluntary or third sector organisations Crew (officially Crew 2000) are working furiously to try and make sense of what this new situation around Covid-19 means. We know how quickly drug trends can change under normal circumstances and how people’s mental health is inextricably connected to how, when, where and why drugs are taken. Our ability to critically assess what is happening for people right now, and where we are as an organisation, has never been more important.We need to know what is happening for people we support and what their continuing, changing or emerging needs are; what services we can provide and which need to change; how we work flexibly to meet these shifting times while minding the needs of our colleagues and ourselves, all of us dealing with our new specific set of challenges, We need to use our knowledge to consider potential fluctuations to supply, and changes in demand, as people are faced with a myriad of triggers and anxieties.